Evaluación del efecto antibacteriano del gluconato de clorhexidina y amonio cuaternario como tratamiento del biofilm en el sistema de irrigación de las unidades dentales - Munive Méndez, Arnaldo Alfredo (2015)
Objetive: The aim of this study was to evaluate the antibacterial effectiveness of chlorhexidine gluconate (0.12 %) ,quaternary ammonium (10%) and distilled water for the biofilm treatment of the irrigation system of dental units measured at day 0 (first day), third and seventh day. Materials and methods: Dental units were divided according the application of the substance (chlorhexidine gluconato, quaternary ammonium and distilled water) and the measurement was made before application of the counting colony-forming units per milliliter (CFU/ml) (day 0) and after application of substances in two times (third and seventh day). The measurement consisted of taking water samples from the triple syringe of 40 dental units from the “Clínica Docente UPC”, then the samples were cultivated on MacConkey agar and after 24 hours of incubation CFU/ml were count. The kruskal-wallis test was used to find and analyzed the results. Results: The chlorhexidine gluconate group had an average of 1.94x106CFU/ml 0 day 0.03x106CFU/ml at day three and 0.001x106CFU/ml at day seven, the quaternary ammonium group had an average of 1.13x106CFU/ml at day 0, 0.01x106CFU/ml at day three and 611.11CFU/ml at day seven and the distilled water group had average 1.86x106CFU/ml at day 0, 1.89x106CFU/ml at day three and 1.65x106CFU/ml at day seven of application. Statistically significant differences were found. Conclusion: The quaternary ammonium had a greater antibacterial effect than chlorhexidine and distilled water. This products can be an alternative to control bacterial levels in dental units.